2020
DOI: 10.1158/2159-8290.cd-19-0959
|View full text |Cite
|
Sign up to set email alerts
|

Selective Alanine Transporter Utilization Creates a Targetable Metabolic Niche in Pancreatic Cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) evolves a complex microenvironment comprised of multiple cell types, including pancreatic stellate cells (PSC). Previous studies have demonstrated that stromal supply of alanine, lipids, and nucleotides supports the metabolism, growth, and therapeutic resistance of PDAC. Here we demonstrate that alanine crosstalk between PSCs and PDAC is orchestrated by the utilization of specifi c transporters. PSCs utilize SLC1A4 and other transporters to rapidly exchange and maintain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 65 publications
(77 reference statements)
1
96
0
Order By: Relevance
“…In pancreatic cancer, SLC38A2 represents the major AAT for alanine, which is then deaminated to pyruvate (which can maintain the tricarboxylic acid cycle) in the presence of pyruvate carboxylase. 56 Finally, our analysis of clinical data from a large breast cancer cohort suggests that high baseline SLC38A2 protein expression correlates with poor BCSS survival in patients with breast cancer and with TNBC. Moreover, tumours with high SLC38A2 expression were also commonly represented in the poor prognostic high SLC cluster (SLC1A5+/SLC7A5+/SLC3A2+).…”
Section: Discussionmentioning
confidence: 88%
“…In pancreatic cancer, SLC38A2 represents the major AAT for alanine, which is then deaminated to pyruvate (which can maintain the tricarboxylic acid cycle) in the presence of pyruvate carboxylase. 56 Finally, our analysis of clinical data from a large breast cancer cohort suggests that high baseline SLC38A2 protein expression correlates with poor BCSS survival in patients with breast cancer and with TNBC. Moreover, tumours with high SLC38A2 expression were also commonly represented in the poor prognostic high SLC cluster (SLC1A5+/SLC7A5+/SLC3A2+).…”
Section: Discussionmentioning
confidence: 88%
“…And as mentioned before, p53 can promote the adaption to glutamine deprivation by increasing arginine uptake through upregulating SLC7A3 in MEFs [37]. Parker et al found that PDAC cells lacking of SLC38A2 were unable to concentrate intracellular alanine and occurred a profound metabolic crisis which lead to markedly impaired tumor growth [117]. In addition, LKB1 can activate AMP-activated protein kinase (AMPK) and inhibit Acetyl-CoA carboxylase (ACC), which is a product in the first step of fatty acid (FA) synthesis, thus inhibiting FA synthesis and tumor growth in lung cancer mouse models [118,119].…”
Section: Discussionmentioning
confidence: 87%
“…While glutamate levels between the two media are comparable, HPLM contains the three remaining components at concentrations at least 5-(aKG), 15-(pyruvate), and 200-fold (alanine) greater than those quantified in RPMI +dS ( Figure 3G). Studies in human cancer cells over the past decade have highlighted a role for GPT2 in facilitating glutamine anaplerosis via the production of aKG (Hao et al, 2016;Kim et al, 2019;Smith et al, 2016;Weinberg et al, 2010), and further, others have reported that GPT can serve to fuel the TCA cycle in certain cancers by catabolizing alanine to pyruvate (Parker et al, 2020;Sousa et al, 2016). Therefore, we considered whether the differential availability of either aKG or pyruvate could explain the RPMI-essential phenotype of GPT2 deletion.…”
Section: Identification Of a Gene-nutrient Interaction Between Gpt2 Amentioning
confidence: 99%